UPAYA PEREMPUAN KARIER DALAM MEWUJUDKAN KELUARGA SAKINAH (Studi Kasus Hakim Perempuan Di Pengadilan Kota Bengkulu) - Santi Susanti (IAIN Bengkulu, 2018)
The purpose of this research is to know the efforts of female judges in realizing happy family. The research was conducted in Bengkulu City Court, March-June 2017. The research method used was survey method and data retrieval technique was done by observation and open interview. Data were analyzed descriptively qualitative. The results show that there are women’s judges to realize their family, including building effective communication, keeping commitments to put aside the suspicion, willingness to give up the right to receive income, paying household assistants to do housekeep- ing, increasing the intensity of romanticism in the household, controlling emotions, supporting the wife’s career, strength- ening religious knowledge in the family, equating perception